Study on energy efficiency using building information modelling (BIM) at shared library Pagoh higher education hub - Anies Faziehan Zakaria; Nurdalila Saji; Mohd Fahmi Abdul Rahman; Kamarul Aini Sari; Mohd Syafiq Syazwan Mustafa; Fatimah Mohamed Yusop (Penerbit Universiti Kebangsaan Malaysia, 2022)
Structures in Malaysia, particularly commercial buildings, have been exceeding the benchmark of building energy usage over the past few years. By maintaining thermal comfort of building under hot climate in Malaysia, air-conditioning system became a basic demand which incessantly operating to fulfil comfort requirement for the occupants in the library. Regards to this, research on energy efficiency using Building Information Modelling (BIM) software by simulating energy analysis was carried out in order to increase energy efficiency of the library. Mineral wool and Polyurethane Foam (P.U.F.) are the materials which proposed to apply in existing wall of building as the thermal insulation layer to increase thermal resistance when external heat transfer through the walls. The Objective of the study is to determine the existing building energy consumption and compare with energy analysis of mineral wool and polyurethane foam. The findings of the building energy analysis simulated by Green Building Studio (GBS) are then compared to discover the most appropriate walls for reducing the building’s energy consumption. P.U.F with its characteristics of high R-value and low U-value, obtain the most effective energy analysis which provide benefits of lowering total annual energy consumption of 294,651 , total annual energy cost of RM 107,645, and energy use intensity (EUI) of 121.7.